(untitled) - Saintenoy, Albane; Léger, Emmanuel (Comptes Rendus. Géoscience, 2025)
Ground-Penetrating Radar (GPR) provides high-resolution, non-invasive insights into the subsurface, making it an essential tool for assessing climate change impacts and managing infrastructure in Arctic and sub-Arctic environments. This review examines GPR applications in mapping and characterizing cold-region features to enhance our understanding of the Critical Zone at high latitudes. Specifically, we focus on permafrost, including its active layer and embedded ice structures, as well as glaciers and front moraine, ice sheets, and snow cover. Furthermore, driven by advancements in miniaturization and energy efficiency, we extend our review to GPR-based subsurface exploration on the Moon and Mars, where environmental conditions and frozen geomorphological structures share similarities with terrestrial cold regions. Finally, we highlight the interconnection between hardware and software advancements and the expanding applications of GPR in cryospheric research.